An investigation on the impact of Kurera/ukondla youth fund on youth livelihoods: a case of Mzilikazi district Bulawayo Metropolitan province - Ncube, Percy Ndumiso (Midlands State University, 2015)
In Zimbabwe youth constitute a large percentage of the population and they are most marginalised group of people when it comes to resource allocation. As result their livelihoods have been affected by lack resources, capabilities and assets to improve their livelihoods. However the Zimbabwe government has made numerous efforts to improve the livelihoods of youth. One of the efforts done by the Zimbabwean government is to create the Ministry of Youth, Indigenisation and Economic Empowerment with the mandate of empowering youth economically, socially and politically. To further buttress and address challenges faced by youth the indigenisation policy was formulated to reduce unemployment, to promote a culture of entrepreneurship, improve resource allocation and improve the livelihoods of young people. Thus the mandate of the Ministry of Youth, Indigenisation and Economic Empowerment is to execute and review policies relating to youth empowerment and compliance with the national indigenisation and economic empowerment. The Zimbabwean government has created national indigenisation policy were the policy has led to the creation of a Youth Fund known as Kurera/Ukondla Youth Fund which is meant to empower indigenous youth of Zimbabwe. The youth aged 18 to 35 years are the main beneficiaries of the youth fund. However, despite the availability of the Kurera/Ukondla youth fund, youth livelihoods remains questionable and has been greatly politicised, thus failing to bring the intend results regardless of government efforts to improve the livelihoods of youth